Is France a restructuring case or Germany? - Gustav A. Horn; Sebastian Watzka (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2018)
This Policy Brief compares macroeconomic developments in France and Germany since the beginning of monetary union. Although the French economy has been growing slower than the German economy since the financial crisis, the two economies have grown at roughly the same rate since the beginning of monetary union. A comparison of the two labour markets also provides a more complex picture than commonly assumed: France has a much higher unemployment rate than Germany, but the volume of work (total hours worked) has increased more since the beginning of monetary union than in Germany. Finally, it is noticeable that domestic demand in Germany has slowed growth for a long time while it played a significant role in France. This changed only in the recent upswing after the financial crisis. This upswing in Germany has also been much more balanced than before. From a pan-European perspective, it is important that the labour market reforms of the Macron government maintain the balance of power in the French labour market. In Germany, on the other hand, the path taken by more expansionary fiscal and wage policy should be systematically continued in order to bring the inflation path back to the ECB's target. – – Der Policy Brief vergleicht die makroökonomischen Entwicklungen Frankreichs und Deutschlands seit Beginn der Währungsunion. Zwar wächst die französische Volkswirtschaft seit der Finanzmarktkrise schwächer als die deutsche, aber seit dem Beginn der Währungsunion sind die beiden Volkswirtschaften bis heute in etwa gleich stark gewachsen. Auch ein Vergleich der beiden Arbeitsmärkte liefert ein komplexeres Bild als gemeinhin angenommen: So hat Frankreich zwar eine deutlich höhere Arbeitslosenquote als Deutschland, aber das Arbeitsvolumen (gearbeitete Stunden) ist dort seit Beginn der Währungsunion stärker gestiegen als in Deutschland. Schließlich fällt auf, dass die inländische Nachfrage in Deutschland über lange Zeit bremsend auf das Wachstum wirkte, während sie in Frankreich eine bedeutende Rolle spielte. Dies änderte sich erst im jüngsten Aufschwung nach der Finanzkrise. Inzwischen ist auch dieser Aufschwung in Deutschland deutlich balancierter als zuvor. Aus gesamteuropäischer Sicht ist es nun von Bedeutung, dass die Arbeitsmarktreformen der Regierung Macron die Machtbalance auf dem französischen Arbeitsmarkt erhalten. In Deutschland sollte hingegen der eingeschlagene Weg expansiverer Fiskal- und Lohnpolitik konsequent fortgesetzt werden, um den Inflationspfad zurück auf die Ziellinie der EZB zu bringen.
urn:nbn:de:101:1-2019022615180753971777
Keywords: 330